Hundreds Dying Every day in Karachi as Pakistan Battles Brutal Summer - Hussain, Remsha; Kabir, Russell (Queeva Publishing, 2024)
Global health and livelihoods have been severely impacted by climate change, which is expected to worsen in the future and bring more frequent and intense extreme events (Weiskopf et al,2020). Extreme heatwaves are increasingly common during summertime globally, contributing to an excess of mortality. As climate change continues, it is anticipated that heat-related illness and mortality will rise even more, with higher levels of global warming being associated with greater risk (Ebi et al,2021). Pakistan ranks sixth among nations most susceptible to the effects of climate change (Soomro & Shahid,2024).According to the IPCC, surface temperatures have risen by roughly 1.0°C since the middle of the 19th century and could climb by 1.10°C to 6.40°C in the 21st (IPCC,2018). Pakistan is extremely sensitive to the consequences of climate change as a developing nation, including rising temperatures, variable monsoons, melting Himalayan glaciers, and more frequent and severe extreme weather events. Future disturbances to Karachi's local weather are anticipated because of climate change (Babar et al, 2021). According to a recent BBC report, Pakistan's heatwave has claimed the lives of nearly 500 people. There has been a notable rise in mortality in southern Pakistan due to temperatures above 40°C (104°F) and heavy humidity, which makes it feel like 49°C (120°F). With 141 deaths on 25th May alone, the Edhi ambulance service reported transporting 568 bodies, as opposed to the typical 30 to 40 each day to the Karachi municipal mortuary over the course of six days. The number of persons requesting assistance in hospitals is rising. Each case's precise cause of death is still being investigated (BBC, 2024). According to Soomro and Shahid (2024), Karachi recorded the hottest temperature in the region last month, with the province of Sindh clocking close to 52.2°C. The extreme heat is making life difficult for people in other parts of Pakistan as well. Low winds, high temperatures, and high humidity are the factors that cause heatwaves. When combined with malfunctioning water supply networks, frequent power plant outages, and blackouts, the consequences for those in lower socioeconomic categories in Karachi can be catastrophic. Conversely, in wealthy Karachian areas where petrol generators are typically used to break out blackouts, very few casualties were reported (Hanif, 2017). Pakistan is classified as a mediocre performer with a climate performance ranking of 30th overall. It receives high marks for GHG emissions and energy use, but poor marks for climate policy and very low marks for renewable energy. The absence of strong government organizations devoted to climate concerns impedes efforts despite the urgent need for climate action (SDG 13). As a result, not enough progress has been made in combating climate change (CCPI, 2024). Public health in Karachi would be much improved by addressing issues with cheap, clean energy, sustainable cities and communities, clean water and sanitation, responsible consumption and production, and climate action. Focusing on important problems like dirty water, air pollution, brittle infrastructure, and energy scarcity. Controlling infectious disease outbreaks and lowering respiratory and cardiovascular illnesses associated with air pollution would be made possible by proper sewage and water cleanliness. Heat stroke casualties could be saved by using inexpensive, sustainable energy technologies. These upgrades are the need to solve the environmental and climate-related issues in Karachi. Effective measures must be taken by the government of Pakistan.